Menara 1 Ibu Pejabat Polis Bukit Aman - Ahmad kamal, Firdaus Haikal; Norhadi, Haiqal Haqeemi; Roslan, Muhammad ‘Adi Haikal; Johari, Naufal Hakim (2024)
The Royal Malaysia Police's (RMP) central and highest administrative office is located at Bukit Aman, often known as the RMP Headquarters. Bukit Aman, which is situated in Kuala Lumpur, Malaysia, acts as the tactical and operational core of the nation's law enforcement operations. The very name "Bukit Aman '' means "Hill of Peace," signifying the dedication to upholding law and order, security, and tranquillity across the country. Bukit Aman, the Ibu Pejabat Polis (Police Headquarters), is an essential hub for organising and supervising different facets of public safety, crime prevention, and policing activities. The central office bears the responsibility of devising policies, executing tactics, and guaranteeing efficient communication and cooperation between diverse police units and divisions throughout Malaysia.